2013
DOI: 10.1161/circgenetics.113.000115
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Aldosterone

Abstract: A ldosterone (aldo) plays a key role in the control of sodium and potassium balance in the distal tubule of the kidney, thus regulating water body content and blood pressure (BP). Aldo acts through the mineralocorticoid receptor (MR), which is a ligandactivated transcription factor. Alteration of the aldo and MR signaling cascade leads to salt-wasting syndromes or hypertension. Clinical Perspective p 390In addition to their role in fluid and electrolyte homeostasis, aldo and MR are important factors for organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Despite high aldosterone levels, cardiac and vascular remodeling, evaluated by gold standard approaches (cardiac MRI, ultrasound, and aortic pulse wave velocity) were not significantly different between MR mutation carriers and noncarriers. 6 These observations support the hypothesis that, in humans, MR is the main receptor involved in aldosterone effect. However, the renal loss of sodium associated with this disease could, per se, explain the observed defect in cardiovascular remodeling.…”
Section: See Related Article P 520-526supporting
confidence: 77%
“…Despite high aldosterone levels, cardiac and vascular remodeling, evaluated by gold standard approaches (cardiac MRI, ultrasound, and aortic pulse wave velocity) were not significantly different between MR mutation carriers and noncarriers. 6 These observations support the hypothesis that, in humans, MR is the main receptor involved in aldosterone effect. However, the renal loss of sodium associated with this disease could, per se, explain the observed defect in cardiovascular remodeling.…”
Section: See Related Article P 520-526supporting
confidence: 77%
“…Older children are generally clinically asymptomatic. Nevertheless, a recent case-control study investigating 39 adult patients with renal PHA1 carriers of NR3C2 mutations showed that they show lifelong increased plasma renin and aldosterone levels as well as increased salt appetite, with normal blood pressure and potassium levels (Escoubet et al 2013), confirming evidence from earlier case reports suggesting persistence of hormonal abnormalities in adulthood (Kuhnle et al 1990, Zennaro et al 1992, Geller et al 2006. Remarkably, high aldosterone levels and salt intake in the context of low MR activity are not associated with adverse cardiovascular outcome in these patients, but rather with improved diastolic left ventricular function (Escoubet et al 2013).…”
Section: Pseudohypoaldosteronism Typementioning
confidence: 58%
“…These and other studies suggest that common functional MR haplotypes are important determinants of inter-individual variability in basal and stress-induced HPA axis activity and stressrelated appraisal and learning, by differentially mediating cortisol effects on different systems (ter Heegde et al 2015). Remarkably, in adult PHA1 patients carrying MR loss-of-function mutations, personal history revealed an increase in depression compared to paired non-carriers (Escoubet et al 2013).…”
Section: Influence Of Mr Gene Variants On Blood Pressure Stress and mentioning
confidence: 68%
See 2 more Smart Citations